Analisis Pintu Bukaan Awal pada Proyek Bendungan Sadawarna terhadap Upaya Mengurangi Banjir Indramayu - M Aziz Isna; Pratikso Pratikso; Abdul Rochim (Jurnal Syntax Admiration, 2024)
The administrative areas of Pramukan District, Pusakajaya District, and Pusakanegara District in Subang Regency, West Java Province, which are located in the downstream part of the Cipunegara Watershed (DAS), are prone to flooding due to the overflow of the Cipunegara River. The impact of flooding can result in the collapse or damage of water structures. The aim of this thesis is to compare the elevation of the openings at the bottom of the Sadawarna Dam. In this research, data collection methods are used in the form of secondary data, literature studies from journals, theses, theses, books and the internet as references for working on this thesis. Analyzing the calculated discharge and hydrograph routing using the Nakayasu method, the maximum elevation to open the early realease door is an elevation of +80.10. If the water has reached an elevation of +80.10 then the early release door will be opened. The Dam Management Unit (UPB) will maintain water at this elevation so that there is no shortage of water and the water level can fall. During the rainy season, the gate will be opened when the water level reaches +80.10. Since the construction of the Sadawarna Dam, flooding in downstream areas, especially in the Indramayu area, has been reduced. The operational pattern of using early release gates also greatly reduces flooding because the water from upstream does not all flow directly downstream, the water is still stored in the dam and its output is measured through the spillway.